2015
DOI: 10.1186/s13045-015-0226-1
|View full text |Cite
|
Sign up to set email alerts
|

Roles of palmitoylation and the KIKK membrane-targeting motif in leukemogenesis by oncogenic KRAS4A

Abstract: BackgroundWe have previously shown that palmitoylation is essential for NRAS leukemogenesis, suggesting that targeting RAS palmitoylation may be an effective therapy for NRAS-related cancers. For KRAS-driven cancer, although much research has been focused on the KRAS4B splice variant, which does not undergo palmitoylation, KRAS4A has recently been shown to play an essential role in the development of carcinogen-induced lung cancer in mice and to be widely expressed in human cancers. However, the role of palmit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 37 publications
(51 reference statements)
0
24
0
Order By: Relevance
“…A similar approach to investigate palmitoylation of KRAS4A G12D in leukemogenesis revealed that even in the absence of palmitoylation, the polybasic region cooperates sufficiently with prenylation to promote disease, albeit with a notable delay in disease onset (82). …”
Section: Constitutive C-terminal Modifications: Membrane Association mentioning
confidence: 99%
“…A similar approach to investigate palmitoylation of KRAS4A G12D in leukemogenesis revealed that even in the absence of palmitoylation, the polybasic region cooperates sufficiently with prenylation to promote disease, albeit with a notable delay in disease onset (82). …”
Section: Constitutive C-terminal Modifications: Membrane Association mentioning
confidence: 99%
“…K-Ras4b has attracted most of the attention because it was assumed to be the more abundant and thus the more important K-Ras isoform mutated in human cancers. However, recent studies have revealed that K-Ras4a is widely expressed in many cancer cell lines and its level is similar to that of K-Ras4b in human colorectal tumors ( Tsai et al, 2015 ; Zhao et al, 2015 ). A requirement for oncogenic K-Ras4a in lung carcinogenesis has also been demonstrated in mice ( To et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…NRAS, HRAS, and KRAS4A are further palmitoylated on the Golgi, increasing their affinity to bind the plasma membrane (16,17). We have shown previously that interrupting the plasma membrane localization of NRAS and KRAS4A could significantly abrogate their leukemogenic potential (18)(19)(20). However, the exact mechanism of RAS proteins translocating from endomembranes to the plasma membrane is still elusive (17).…”
Section: Introductionmentioning
confidence: 99%